Citizen's handbook on environmental protection. - Local Government Development Foundation (Manila Local Government Development Foundation, 2000)
This handbook attempts to provide individual citizens a guide on environmental protection for future use. It contains topics on biodiversity, land use management, forest resources, marine resources, waste management and community education.
Contains scientific explanations about environmental issues in the Philippines. Topics are followed by suggestions on what actions individual Filipinos should take to alleviate the problem.
"Originally published in English and translated in Nippongo by ICLEI, Asia-Pacific Secretariat, Tokyo, Japan."
Jointly published by Konrad Adenaur Stiftung in cooperation with Federation of Canadian Municipalities and International Council for Local Enviromental Initiatives.
Keywords: Environmental protection -- Citizen protection -- Handbooks, manuals, etc